2018
DOI: 10.3390/ma11081416
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Spectroscopy for In Situ Monitoring of Porous Materials Formation under Hydrothermal Conditions

Abstract: The employment of nuclear magnetic resonance (NMR) spectroscopy for studying crystalline porous materials formation is reviewed in the context of the development of in situ methodologies for the observation of the real synthesis medium, with the aim of unraveling the nucleation and growth processes mechanism. Both liquid and solid state NMR techniques are considered to probe the local environment at molecular level of the precursor species either soluble in the liquid phase or present in the reactive gel. Beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…[13] Also, Haouas compared MIL-101(Cr) synthesis in water against DMF and observed that solvent effects are key to determine the final MOF structure. [10,14] Taddei also described SBU formation as a key step in MOF synthesis. [10] Working on MIL-53 Embrechts et al identified the rearrangement of soluble MOF precursors as the rate-limiting step in MOF synthesis.…”
Section: Doi: 101002/adts202000092mentioning
confidence: 99%
“…[13] Also, Haouas compared MIL-101(Cr) synthesis in water against DMF and observed that solvent effects are key to determine the final MOF structure. [10,14] Taddei also described SBU formation as a key step in MOF synthesis. [10] Working on MIL-53 Embrechts et al identified the rearrangement of soluble MOF precursors as the rate-limiting step in MOF synthesis.…”
Section: Doi: 101002/adts202000092mentioning
confidence: 99%
“…Therefore, during the last years, many efforts have been focused on the development of different techniques for the investigation of hydrothermal synthesis in situ. [14][15][16][17][18][19][20] Among the in situ spectroscopic techniques, MAS NMR is one of the most informative, since it is based on the direct observation of atomic nuclei, which compose the frameworks of reagents, products and intermediates during the synthesis and therefore provides a unique advantage to probe the local structure at the molecular level and to access the crystallization process from the very beginning. Besides that, it allows distinguishing between different species in solution and solid state, which is not possible by other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…41 The synthesis of various materials including MOFs can be monitored by in situ liquid-state and solid-state NMR spectroscopy as reviewed by Haouas. 42 An elegant combination of liquid-and solid-state NMR spectroscopy is denoted as CLASSIC (combined liquid-and solid-state in situ crystallization). It is performed on identical samples under MAS by interleaved detection of directly excited and crosspolarization spectra.…”
Section: Experiments Under Masmentioning
confidence: 99%